2019
DOI: 10.1096/fj.201901080r
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial metabolite butyrate protects against proteinuric kidney disease through epigenetic‐ and GPR109a‐mediated mechanisms

Abstract: Butyrate is a short‐chain fatty acid derived from the metabolism of indigestible carbohydrates by the gut microbiota. Butyrate contributes to gut homeostasis, but it may also control inflammatory responses and host physiology in other tissues. Butyrate inhibits histone deacetylases, thereby affecting gene transcription, and also signals through the metabolite‐sensing G protein receptor (GPR)109a. We produced an mAb to mouse GPR109a and found high expression on podocytes in the kidney. Wild‐type and Gpr109a–/– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 60 publications
(92 reference statements)
1
59
0
Order By: Relevance
“…Uropathogenic Escherichia coli, the leading pathogen of urinary tract infections (UTIs) or hemolytic uremic syndrome, contributes to kidney injury through alphahemolysin or Shiga toxin [51], and a 1% relative gut abundance of Escherichia is an independent risk factor for Escherichia bacteriuria and UTI [52]. Depletion of the genera Prevotella, Roseburia, Faecalibacterium, and Coprococcus may result in less production of butyrate [22] which is known to have renal protection effects [53]. Genus Bifidobacterium was depleted in CKD patients, and supplementing Bifidobacterium longum reduced serum creatinine, urea nitrogen, and PCS in CKD models [54].…”
Section: Discussionmentioning
confidence: 99%
“…Uropathogenic Escherichia coli, the leading pathogen of urinary tract infections (UTIs) or hemolytic uremic syndrome, contributes to kidney injury through alphahemolysin or Shiga toxin [51], and a 1% relative gut abundance of Escherichia is an independent risk factor for Escherichia bacteriuria and UTI [52]. Depletion of the genera Prevotella, Roseburia, Faecalibacterium, and Coprococcus may result in less production of butyrate [22] which is known to have renal protection effects [53]. Genus Bifidobacterium was depleted in CKD patients, and supplementing Bifidobacterium longum reduced serum creatinine, urea nitrogen, and PCS in CKD models [54].…”
Section: Discussionmentioning
confidence: 99%
“…There was a greater effect as time progressed perhaps indicating adaptation to RS consumption. On a molar basis, RS is a particularly efficient precursor of butyrate production [ 59 ] and has been shown to ameliorate proteinuria in a mouse model of CKD [ 60 ], aspects that may be beneficial to diabetic cats, which have a paucity of butyrate-producing bacteria in their microbiome [ 61 ]. Increased fecal butyrate in the HRS diet group indicates the potential for dietary RS to exert a benefit in cats.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a diet rich in acetate and butyrate protected mice against T1D and this SCFA-induced protection happened via changes in gut/immune regulation, expanding T reg cells and reducing pathogenic B cells, CD4+, and CD8+ T cells [107]. Butyrate impairs progression of nephropathy through, at least in part, protective effects on podocytes mediated by DNA methylation and Histone Deacetylases (HDACs) -dependent mechanisms, involving genes essential for podocyte function, as well as activation of GPR109a [108]. Donohoe et al demonstrated that, in gnotobiotic mice colonized with wild-type or mutant strains of butyrate-producing Butyrivibrio fibrisolvens, a fiber-rich diet induced strong tumor-suppressive effects in a microbiota-and butyrate-dependent manner.…”
Section: Diet Microbiota Metabolites and Dna Methylationmentioning
confidence: 99%